Kerinci District Government's Efforts to Develop Inclusive Education in Remote Areas: Challenges and Strategies - Dirgantara, Mario (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
Inclusive education ensures that all children, including children with special needs, have access to quality education. Although national policies support inclusive education, many challenges still hinder its implementation in remote areas. This article discusses local government efforts to improve inclusive education in remote areas, problems encountered and solutions. Data were collected by conducting literature research and policy analysis. Results show that local governments have done a lot to improve infrastructure, improve teacher training, provide a special budget and disseminate information to the community. Challenges such as infrastructure shortages, teacher shortages, and lack of public awareness still need to be addressed. The article concludes that the main strategies for improving inclusive education in remote areas are inter-sectoral cooperation, strengthening the role of communities and developing sustainable models.